Corruption and firm performance: Evidence from Greek firms - Daphne Athanasouli; Antoine Goujard; Pantelis Sklias (International Journal of Economic Sciences and Applied Research, 2012)
This article investigates the relationship between corruption and firm performance in Greece using firm level data. Corruption is overall negatively associated with firm size and growth at the firm level. We focus on the effect of 'administrative corruption', whereby firms engage in corrupt practices and bribery of government officials. We contrast the firm experience of corruption and the contextual experience of corruption at the sectoral level and find that the latter, contextual corruption is more important. The contextual effect of corruption identifies the magnitude of systemic corruption in Greece, indicating the need for reforms in an institutional environment that allows corrupt practices. Furthermore, firms of different size appear differently affected by corruption. This suggests that firm engagement in corruption is heterogeneous. Using quantile regressions, small and medium firms display a higher engagement in corrupt practices. However, their performance is less correlated with corruption than that of large firms.
Keywords: D73; O17; M21; 330: bribery; corruption; growth; firm size; Greece; Korruption; Unternehmenserfolg; Betriebsgröße; Griechenland